Notch signaling: the demise of elegant simplicity - Kadesch, Tom (Current opinion in genetics & development, 2004)
Notch signaling can be viewed as an elegantly simple pathway that begins when the Notch receptor binds ligand, and ends when the Notch intracellular domain enters the nucleus and activates transcription. However, it is becoming increasingly clear that this core pathway is subject to a wide array of regulatory influences, from those that affect ligand–receptor interactions to those that govern the choice of Notch target genes. Even Notch ligands are now being scrutinized with respect to the possibility that they, too, function in the nucleus. A complete understanding of Notch signaling therefore requires us to look well beyond the core pathway.